Cooperação entre um robô aéreo e um robô terrestre para identificação de rotas livres em solo - Sá, Fabricio Bortolini de (2014)
This Masters Thesis addresses the problem of cooperation between an aerial and a terrestrial robots in outdoor environments using nonlinear control and image processing techniques. The idea is to implement a system that allows the terrestrial robot to navigate in a map previously known, being able to avoid obstacles and to recalculate its route after the aerial robot, or the terrestrial robot, identifies an obstruction on the road. For this, the robots should be able to determine which path they will follow, to detect obstacles and to exchange information. The obstacle detection and the landmarks identification by the terrestrial robot are performed using, respectively, a laser sensor and image processing, while the aerial robot performs the same activities using only image processing. The advantage of performing a cooperation between a terrestrial robot and an Unmanned Aerial Vehicle (UAV) is the optimization of the terrestrial robot navigation time by processing the images captured by the aerial robot. This processing will allow an early detection of adversities on the route of the terrestrial vehicle and also the landmarks in this same route. Controllers for point to point navigation and for obstacle avoidance were implemented. A method to perform the correction of the terrestrial robot’s odometry was also developed. In addition, a simulator for the mobile robot and also a communication interface between the two robots were developed. Finally, experimental tests were performed in outdoor environments in order to verify the effectiveness of the developed system. Through the results achieved with the tests, the effectiveness of the proposed system was comproved. The robots were able to navigate until reaching the destination point, the terrestrial robot was able to avoid the obstacles and also to recalculate its path when an obstruction on the route was found either by the aerial robot or by itself.